Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization